Failure Behaviour Of 3D-Printed ABS Lattice Structure Under Compression - Hasan, Rafidah; Rosli, Nur Ameelia; Mat, Shafizal; Alkahari, Mohd Rizal (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Lattice structure is a lightweight material that can be produced using the cutting edge additive layer manufacturing process or also known as 3D printing. Lattice structure material is a periodic cellular structure material that can be utilized in various applications especially as core material in sandwich structure configuration, where the ultimate aim is to be a lightweight material with load bearing capability. Researches are yet to be done to fully understand the behavior of lattice structure materials under several loading conditions such as tensile, bending and compression. The objective of this paper is to discuss the behavior of acrylonitrile-butadiene-styrene (ABS) lattice structure material that was produced using the layer by layer manufacturing, subjected to compressive load. Lattice structure specimens with dimension 20x20x20 mm3 were designed with body centered cubic (BCC) unit cells for three sets of strut diameter size. The specimens were produced using fused deposition modelling (FDM) Cubepro 3D printer, with varying default parameters of layer thickness, print strength and print pattern. All specimens were subjected to compressive load until densification stage and the stress-strain curves of the material were plotted. The compressed specimens were observed under an optical digital microscope and a common failure behavior of 3D-printed ABS lattice structure material was highlighted. It was shown that the failure of compressed lattice structure was initiated at joint node areas due to bending tensile stress. It can be concluded that this polymer material showed hybrid between stretch and bending-dominated characteristics. This is a good indicator for lightweight material with load absorbing capability. An understanding in the failure behavior of ABS lattice structure material is enriching the knowledge on this material under stress-strain condition.